2022
DOI: 10.1101/2022.04.30.22274239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

GALCvariants affect galactosylceramidase enzymatic activity and risk of Parkinson’s disease

Abstract: The association between glucocerebrosidase (GCase), encoded by GBA, and Parkinson's disease highlights the role of the lysosome in Parkinson's disease pathogenesis. Genome-wide association studies (GWAS) in Parkinson's disease have revealed multiple associated loci, including the GALC locus on chromosome 14. GALC encodes the lysosomal enzyme galactosylceramidase (GalCase), which plays a pivotal role in the glycosphingolipid metabolism pathway. It is still unclear whether GALC is the gene driving the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Deficiency in TMEM175 leads to lysosomal overacidification, impaired proteolytic activity, and increased aggregation of α-synuclein. Senkevich et al 2023 identified an association between the GALC gene, which encodes the lysosomal enzyme galactosylceramidase, and PD (Senkevich et al 2023). The research demonstrated that a specific variant in the GALC locus is associated with increased galactosylceramidase activity and PD.…”
Section: Lysosomal Factors In Pd Pathogenesismentioning
confidence: 99%
“…Deficiency in TMEM175 leads to lysosomal overacidification, impaired proteolytic activity, and increased aggregation of α-synuclein. Senkevich et al 2023 identified an association between the GALC gene, which encodes the lysosomal enzyme galactosylceramidase, and PD (Senkevich et al 2023). The research demonstrated that a specific variant in the GALC locus is associated with increased galactosylceramidase activity and PD.…”
Section: Lysosomal Factors In Pd Pathogenesismentioning
confidence: 99%